DEVELOPMENT OF AN INFORMATION SYSTEM FOR DECISION SUPPORT AND AUTOMATION OF CONTROL OF TV3-117 AIRCRAFT ENGINE IN CRITICAL SITUATIONS BASED ON KNOWLEDGE ENGINEERING - Vladov, Serhii; Shmelov, Yurii; Dieriabina, Inna; Podhornykh, Nadiia; Shmelova, Tetiana (Proceedings of National Aviation University (archive), 2020)
Purpose: The purpose of this article is to develop an information system for decision support and automation of control of the aircraft engine TV3-117 in critical situations based on knowledge engineering. Methods: The following methods are applied in the article: simulation modeling method at the stage of designing an information system for decision support; special methods and means of object-oriented modeling of the subject area, which are developed for the design of information systems in order to recreate the conceptual model of experts in a formalized model of knowledge representation; hierarchical search method to search for use cases; ontological analysis with the aim of identifying and combining relevant information-logical and functional aspects of the system under study. In the modeling process, paradigmatic relationships are established between the cognitive elements of the process of controlling a complex dynamic object in critical situations (cause-effect, similarities), as well as generalization, association, depending on the implementation, necessary for the development of a complex of object-oriented models of the control process. Results: The conducted studies show that an additional analysis of all the possibilities of the applied knowledge representation models is needed to solve specific problems in the considered problem area. The methodology of object-cognitive analysis is the basis for creating an information system for decision support, including the intellectual component of the acquisition, accumulation, processing, provision, updating and dissemination of knowledge. The obtained object-oriented models of the subject area and ontology of the decision support system are the basis for the development of methods and algorithms for finding management solutions in critical situations. Discussion: The results obtained are applied within the framework of the concept of intellectualizing the process of control and diagnostics of the TV3-117 aircraft engine technical state in flight modes, one of the points of which is the intellectual processing and storage of information about the results of flight tests and operation of the TV3-117 aircraft engine based on the requirements of modern databases and knowledge bases, with the possibility of their integration into modern CASE-technologies.